2021
DOI: 10.1155/2021/3060375
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α Is Associated with Resistance to Hypoxia-Induced Apoptosis in Ameloblastoma

Abstract: Background. Ameloblastoma (AMB) is a benign odontogenic tumour, with an aggressive local behaviour and a high rate of recurrence. Previous studies have demonstrated that hypoxia-induced factor alpha 1 (HIF-1α) and activated caspase-3 contribute to tumour invasiveness and cytogenesis in ameloblastoma. Hypoxia increases HIF-1α levels, which triggers a number of signalling pathways. This paper aimed to present data in the study of hypoxia-activated signalling pathways that modulate proapoptotic and antiapoptotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…In summary, these data suggested that α-hederin overcomes hypoxia-mediated resistance in CRC cells in vivo through the AKT/Bcl2 signalling pathway. between HIF-1α and Bcl2 (21). Herein, the expression levels of Bcl2 and Bcl-xL were observed to be positively correlated with the expression levels of HIF-1α in the collected clinical tissue samples, as demonstrated by IHC experiments, indicating that apoptosis inhibition was positively correlated with hypoxia (Fig.…”
Section: α-Hederin Overcomes Drug Resistance In Crc Cells Under Hypox...mentioning
confidence: 56%
“…In summary, these data suggested that α-hederin overcomes hypoxia-mediated resistance in CRC cells in vivo through the AKT/Bcl2 signalling pathway. between HIF-1α and Bcl2 (21). Herein, the expression levels of Bcl2 and Bcl-xL were observed to be positively correlated with the expression levels of HIF-1α in the collected clinical tissue samples, as demonstrated by IHC experiments, indicating that apoptosis inhibition was positively correlated with hypoxia (Fig.…”
Section: α-Hederin Overcomes Drug Resistance In Crc Cells Under Hypox...mentioning
confidence: 56%
“…However, these cells are equidistant from the surrounding bone matrix so they would not receive as much stimulus resulting from bone resorption. Additionally, some studies have shown that in tumour microenvironments with hypoxia, there is an increase in apoptosis and the formation of cystic areas in the central portions of the CAM [10,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, tumour cells typically demonstrate high demand for oxygen during proliferation, and access to oxygen in the central area of the tumour becomes restricted, which leads to the creation of hypoxic microenvironments [10]. This process occurs in most solid tumours and can result in an increase in aggressiveness at the front of tumour invasion (tumour periphery) [24] or lead to tumour death by apoptosis in the centre of the tumour [22]. This validates the result of quanti cation in different regions of the MUA, in which the highest rates of immunostaining for the apoptosis-promoting protein were found in the cystic lumen region (tumour centre).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ameloblastoma cell line was cultured and maintained in culture bottles according to Valladares et al (2021) .…”
Section: Methodsmentioning
confidence: 99%